Pengaruh Citra Rizal Wahid dan Kualitas Pelayanan Terhadap Minat Keikutsertaan - Faruqi, Rijal; Batu, Reminta Lumban (Peneliti.net, 2025)
This study analyzes the influence of Rizal Wahid's image and service quality on the interest of participants in the Quran Festival FKDK Unsika. This festival aims to increase love for the Qur'an, but faces obstacles in the small number of participants. This is influenced by the image of the lesser-known speaker and the inadequate quality of service. This research method is quantitative with descriptive and verification analysis. The population was Quran Festival participants, with a sample of 76 respondents using purposive sampling. Data were analyzed using multiple linear regression. The results showed that Rizal Wahid's image had a negative effect of 8.6%, while service quality had a positive effect of 49.7%. Simultaneously, these two variables have an effect of 60.8% on participant interest, with 39.2% influenced by other factors not studied.